Hubungan Antara Penerapan IT Governance Dengan Kepuasan Pengguna Sistem Informasi Akademik - Restiani, Ni Kadek Ita; kusuma, Dewa Gede Adi; Indriyani, Indriyani (Jurnal Tata Kelola dan Kerangka Kerja Teknologi Informasi, 2025)
ABSTRACT – The utilization of information technology (IT) in the field of education has become a crucial factor in enhancing the efficiency and effectiveness of academic administration processes. Academic information systems (AIS) are now widely used to manage student data, class schedules, academic grades, and other information related to educational processes. A journal titled The Relationship Between IT Governance Implementation and User Satisfaction of Academic Information Systems discusses the correlation between user satisfaction and academic system services in higher education institutions. The aim of this study is to identify how the implementation of IT governance relates to user satisfaction with academic information systems. The methods employed include interviews and questionnaires, with the validity and reliability of the questionnaire results tested. Keywords – IT Governance, User Satisfaction, Questionnaires, Interviews.